2012
DOI: 10.1002/uog.9077
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid ovarian carcinoma in a woman with a history of infertility and multiple in‐vitro fertilization treatment cycles

Abstract: Ovarian cancer is rarely diagnosed during assisted reproduction. Several case-control and cohort studies have described its incidence within the infertile population well after the assisted reproductive process. We present a case of endometrioid adenocarcinoma that developed during the ovarian stimulation process and show corresponding ultrasound images of its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some patients experience repeated implantation failure, and approximately 25% had already undergone more than five IVF-ET cycles [ 12 ]. Repeated IVF-ET significantly increases the risk of ovarian hyperstimulation syndrome, premature delivery and oestrogen-dependent tumours [ 41 43 ]. The study also found that anxiety and stress are present in women throughout the treatment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some patients experience repeated implantation failure, and approximately 25% had already undergone more than five IVF-ET cycles [ 12 ]. Repeated IVF-ET significantly increases the risk of ovarian hyperstimulation syndrome, premature delivery and oestrogen-dependent tumours [ 41 43 ]. The study also found that anxiety and stress are present in women throughout the treatment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports indicate that the incidences of ovarian, uterine, and breast cancers are not increasing [47], but it has also been reported that, in actual clinical practice, ovarian cancer rapidly progresses when detected during fertility treatment with ovulation-inducing drugs [8]. We were unable to find any other articles where malignant pheochromocytoma was detected during fertility treatment, and so it is unclear whether or not the ovulation-inducing drugs caused the malignant pheochromocytoma.…”
Section: Discussionmentioning
confidence: 89%
“…15 However, some literature has shown that repeated IVF cycles may significantly increase the risk of ovarian hyperstimulation syndrome, oestrogen-dependent tumors and premature delivery. [16][17][18] Evidence shows that patients who experience repeated IVF failure are more prone to poorer QoL, partly because of the longer duration of conception delay and partly because of the increased IVF medical, emotional and financial burden. 19 Our previous study revealed that women with repeated implantation failure had significantly lower levels of FertiQoL, and anxiety and depression were negatively correlated with FertiQoL.…”
Section: Introductionmentioning
confidence: 99%